A study of figurative languages in the poem Kepada Semua Perempuan yang Membawa Luka Hati written by Asma Nadia - Rini Damayanti; Suprihatien Suprihatien (BAHASTRA, 2021)
This study aims to better understand the meaning contained in a literary work and to recognize the various figurative languages or metaphors found in a literary work. The qualitative descriptive method used in this study is in the form of a review or text analysis of the poem Kepada Semua Perempuan yang Membawa Luka Hati written by Asma Nadia. This poetry study concludes that a woman is indeed demanded to be more courageous, more patient, and more tolerant in dealing with everything. The figurative language used by the author in writing the poem was also diverse, so it has represented several figurative languages that have been commonly used.